Reparative osteogenesis at hyperhomocysteinemia (experimental study). - Bezsmertnyi, Yu. O. (Морфологія / Morphologia / Morfologìâ, 2013)
On the model of fracture of the femur studied peculiarities of reparative osteogenesis at hyperhomocysteinemia and demonstrated the possibility of its correction drugs with hypohomocysteinemia effect. It is established, that hyperhomocysteinemia induces dysregulation of reparative osteogenesis with the formation of large areas of necrosis and degeneration at the fracture site. Metabolic correction of hyperhomocysteinemia preparations with hypohomocystinemic action (decamevitum, glutarginum) optimizes for reparative regeneration of the fracture.